Практична складова освітнього процесу в Національній академії прокуратури України: шляхи удосконалення - Стеценко, Семен Григорович; Стеценко, Семен Григорьевич; Stecenko, Semen (My University, 2009)
In t h e article the main c o m p o n e n t s of educational process in National A c a d e m y of Prosecution of Ukraine are illustrated. It is noticed that practical c o m p o n e n t of educational p r o c e s s have to d o m i n a t e . O p t i m a l b a l a n c e b e t w e e n t h e o r e t i c a l and professional disciplines have to exist.
Стеценко С. Г. Практична складова освітнього процесу в Національній академії прокуратури України: шляхи удосконалення / С. Г. Стеценко // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 252-259.
Keywords: професійна освіта; підготовка спеціалістів юридичного профілю; Національна академія прокуратури України; профессиональное образование; подготовка специалистов юридического профиля; Национальная академия прокуратуры Украины; professional education; preparing of t h e specialists of juridical profile; National Academy of Prosecution of Ukraine